2020
DOI: 10.1186/s13104-020-05167-2
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic activity and brine shrimp lethality of venom from the large brown spitting cobra (Naja ashei) and its neutralization by antivenom

Abstract: Objective: Naja ashei is a snake of medical importance in Kenya, Ethiopia, Somalia, Uganda, and Tanzania. Little is known about the enzymatic (snake venom phospholipases A 2 ; svPLA 2 's) and toxic (lethal) activities of N. ashei venom and crucially, the safety and capacity of available antivenom to neutralize these effects. This study aimed to determine the enzymatic and toxic activities of N. ashei venom and the capacity of Indian and Mexican manufactured antivenoms to neutralize these effects. The protein c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…A final measurement related to the determination of the effect of 3FTx on cell lines was to determine the safety of administration of venom components by determining the LD50. Studies conducted by Okumu et al [ 60 ] have shown a dose-dependent and time-dependent variable toxicity of the components of the Naja ashei venom. The LC50 for this snake venom was 63.02 μg/mL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A final measurement related to the determination of the effect of 3FTx on cell lines was to determine the safety of administration of venom components by determining the LD50. Studies conducted by Okumu et al [ 60 ] have shown a dose-dependent and time-dependent variable toxicity of the components of the Naja ashei venom. The LC50 for this snake venom was 63.02 μg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Based on preliminary results, isotherms for single lipid components were obtained for 10 and 40 ng/mL 3FTx. The cholesterol and phospholipid (PL) ratio for the membrane mimicking system of used human cell lines were 0.35 for HL- 60…”
Section: Model Membranes Compositionmentioning
confidence: 99%
“…As is the case with the other African spitting cobras, the venom of N. ashei is known to induce mainly cytotoxic effects caused by the predominant presence of 3FTx proteins and phospholipases A 2 [ 5 , 6 ]. N. ashei is a medically important snake species in Kenya, Ethiopia, Uganda, Somalia, and Tanzania, and thus, is implicated in snakebites and associated morbidity, mortality, and disability [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, Inoserp™ antivenom consist of venoms of a wider variety of Naja snakes including N. pallida , N. nubiae and N. senegalensis , which are not covered in the specific VINS™ antivenom under review. Nevertheless, according to Okumu and colleagues ( Okumu et al, 2020 ), the venom of N. ashei does not form part of the immunizing mixtures of commercially available antivenoms as of yet. Thus, whereas the neutralizing efficacy of Mexican and Indian-made antivenoms against N. ashei venom phospholipase A 2 activity and venom-induced lethality in the brine shrimp model has been demonstrated ( Okumu et al, 2020 ), the efficacy of these antivenoms to neutralize N. ashei -induced lethal and cytotoxic effects in mice model is not known.…”
Section: Introductionmentioning
confidence: 99%